Segmenting the mature travel market by motivation. (6th November 2008) - Wang, Yawei; Zhang, Yanli; Xia, John; Wang, Zhongxian
The purpose of this study was to segment mature travellers based on their motivations and to profile the similarities and differences between mature travel market segments according to their sociodemographic and travel-related characteristics. A total of 217 respondents (50 years old and above) in the Upstate area in a southern state in the USA were used in this study. Three types of mature travellers were identified with an exploratory factor analysis and cluster analysis: personal, educational and social travellers. They were significantly different regarding the number of years they had lived in the Upstate.